2007
DOI: 10.1002/chem.200601619
|View full text |Cite
|
Sign up to set email alerts
|

The Phenalenyl Motif: A Magnetic Chameleon

Abstract: The 12π cation (3) and 14π anion (4) derived from the phenalenyl radical (2) support diatropic (“aromatic”) perimeter ring currents, but isoelectronic replacement of the central atom by either boron (5) or nitrogen (6) leads to paratropic (“antiaromatic”) current; the ipsocentric approach to molecular magnetic response accounts for all four patterns in terms of competition between translationally and rotationally allowed virtual π–π* excitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 48 publications
5
32
0
Order By: Relevance
“…This analysis also suggests that the corannulene dianion, observed in the 1 H‐NMR as a ‘diamagnetic’ singlet only at low temperatures, is actually a paramagnetic closed‐shell species. A similar analysis of induced ring currents was calculated for phenalenyl ions 70. It was demonstrated that both cation and anion maintain a diatropic ring current in the molecule—despite having 12 and 14 π electrons, respectively.…”
Section: Aromaticity and Antiaromaticity In Polyarene Anionssupporting
confidence: 55%
“…This analysis also suggests that the corannulene dianion, observed in the 1 H‐NMR as a ‘diamagnetic’ singlet only at low temperatures, is actually a paramagnetic closed‐shell species. A similar analysis of induced ring currents was calculated for phenalenyl ions 70. It was demonstrated that both cation and anion maintain a diatropic ring current in the molecule—despite having 12 and 14 π electrons, respectively.…”
Section: Aromaticity and Antiaromaticity In Polyarene Anionssupporting
confidence: 55%
“…The NICS zz -scan curve (Figure 9c) of the phenalenyl cation is typical for aromatic molecules exhibiting pure π-aromatic character. Very recently, Fowler et al [92] using the ipsocentric approach predicted the diatropicity of the phenalenyl cation which arises mainly from the contribution of the doubly degenerate 2e HOMO-2 pair. …”
Section: The Nics Zz -Scan Curves Versus the Orbital-type Of Aromaticmentioning
confidence: 99%
“…It is the smallest polycyclic subunit of graphene with an internal carbon atom and has peculiar and interesting electronic properties. 17,18 It has been invoked as a building block for single molecule molecular conductors, 19,20 and its high stability has led to derivatives having been observed at room temperature in solution and as crystals. 21,22 …”
Section: Introductionmentioning
confidence: 99%